USING SPOT 6 TO ESTIMATE BIOMASS AND CARBON STOCKS OF PINUS MERKUSII PLANTATION IN DINH HAI COMMUNE, THANH HOA PROVINCE - Huu Nghia, Nguyen; Hai Hoa, Nguyen; Thanh An, Le; Thi Ngoc Lan, Tran; Easmin, Amena; Thi Minh Tu, Nguyen (Journal of Forestry Science and Technology, 2017)
This study describes how the Inverse Distance Weighted Interpolation (IDW) in combination with the field-based survey and 2015 SPOT 6 data are applied to estimate biomass and carbon stocks of Pinus merkusii plantation in Dinh Hai commnue, Tinh Gia district, Thanh Hoa province. The construction of current map of Pinus merkusii shows that there is 87.0% of accuracy and accuracy asessment of interpolated maps of biomass and carbon stocks are over 83.0 %, showing this IWD interpolation is reliable and can be applicable in Dinh Hai commune. As a result, the total carbon stocks is estimated at about 1,959,622.4 tons, equivalent to 221,497,194,300 VND in Dinh Hai. Although having high values and potential for carbon stocks trading, the Payments for Forest Environmental Services (PFES) have not been implemented in Tinh Gia district yet. This study also has presented solutions for PFES implementation in Tinh Gia, thus enhancing local livelihoods.